Thiochalcone substituted phthalocyanines for dye-sensitized solar cells: Relation of optical and electrochemical properties for cell performance. Issue 10 (19th May 2018) - Karaca, Hüseyin; Şişman, İlkay and Güzel, Emre and Sezer, Serdar and Selimoğlu, Faysal and Ergezen, Bahar and Karaca, Meryem and Eyüpoğlu, Volkan
Abstract: The new peripherally tetra-substituted metallophthalocyanines (MPcs, M=Zn, Co, Ni) bearing the chalcone, (E)-3-(4-hydroxyphenyl)-1-(thiophen-2-yl)prop-2-en-1-one, for dye-sensitized solar cells (DSSCs) were synthesized. FT-IR, 1 H NMR, 13 C NMR, and UV–Vis spectroscopy techniques were utilized for characterization of all the MPcs. Electrochemical, optical and photovoltaic properties of all the MPcs as sensitizers were examined. Electrochemical studies reveal that while the ZnPc (4 ) and NiPc (6 ) give only Pc ring-based redox reactions, the CoPc (5 ) shows redox reactions based on both the central metal and the ring due to the metal 3d orbitals lying between the Pc HOMO and LUMO. The DSSC based on5 gave the lowest power conversion efficiency (0.51%), perhaps due to the presence of a redox active central metal ion in the core of the complex, which results in a decrease electron transfer in the device. However, cells based on the other complexes including redox inactive central metal ions, which cannot reduce electron transfer, showed reasonable power conversion efficiencies of 1.27% and 1.11% for4 and6, respectively. The slight difference between the efficiencies can be attributed to higher molar extinction coefficient and narrower band gap of4 than6, which ensure a higher photocurrent and broader light absorption in the visible region. Abstract :